PERAN BADAN USAHA MILIK DAERAH SEBAGAI INSTRUMEN INVESTASI PEMERINTAH DAERAH: STUDI KASUS DIVESTASI SAHAM NEWMONT - Disyon, Huta; Riyandi, Marwan; Amalia, Garnita (Faculty of Law, Parahyangan Catholic University, 2024)
The investments made by Local Governments in Regional Owned Enterprises (ROEs) have not yielded satisfactory returns. One potential investment opportunity for Local Governments is participating in the divestment of foreign shareholders in mining companies. This study analyzes the role of ROEs in divesting mining company shares, including the legality of ROE establishment, the position of ROEs in mining company divestment, and their role as investment instruments for Local Governments, using PT Newmont Nusa Tenggara as a case study. Using a normative method and analyzing secondary data descriptively, the study finds that Local Governments must ensure the administrative process of establishing ROEs complies with applicable laws and regulations. ROEs can partner with investors to address funding difficulties in foreign divestment transactions. Additionally, the priority position of Local Governments in divesting foreign shares in mining companies should provide a strong bargaining position in negotiating the establishment of ROEs and subsidiaries used as vehicles in these transactions.